Solid state interdigitated Sb2S3 based TiO2 nanotube solar cells. Issue 47 (28th July 2020) - Büttner, Pascal; Döhler, Dirk; Korenko, Sofia; Möhrlein, Sebastian; Bochmann, Sebastian; Vogel, Nicolas; Mínguez-Bacho, Ignacio; Bachmann, Julien
Abstract : TiO2 nanotubes generated by anodization of metallic titanium sputter-coated on indium tin oxide (ITO) substrates are used as a conductive scaffold for all-solid-state Sb2 S3 -sensitized extremely thin absorber (ETA) solar cells. Abstract : TiO2 nanotubes generated by anodization of metallic titanium sputter-coated on indium tin oxide (ITO) substrates are used as a conductive scaffold for all solid-state Sb2 S3 -sensitized extremely thin absorber (ETA) solar cells. A blocking layer of TiO2 placed between Ti and ITO in combination with optimized Ti deposition and anodization conditions enables the formation of crack-free layers of straight, cylindrical TiO2 nanotubes of tunable length and diameter. ALD (atomic layer deposition) is subsequently used to coat this substrate conformally with a highly pure Sb2 S3 light absorber layer under an inert atmosphere. The high absorption coefficient of Sb2 S3 as compared to molecular dyes allows for the utilization of very short nanotubes, which facilitates the infiltration of the organic hole transport material and formation of a p–i–n heterojunction in an interdigitated and tunable geometry. We investigate the influence of nanotube length and of the absorber thickness to enhance the photocurrent value to twice that of planar reference structures.